Coping Mechanisms of Senior High School Learners During the Covid-19 Pandemic at Goshen School of Technology and Humanities: A Case Study - Bangayan, Daniel Siodina; Ambagan, Florencio; Rosales, Maria Rio Bongabong; Maming, . Jimmy Bernabe (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The pandemic known as the COVID-19 brought global issues in the economy, environment, government, health, technology, and education. In the aftermath, schools around the world have been closed to control the spread of the disease that directly impacted the students, educators, and academic institutions that caused sudden disruptions to all stakeholders particularly on students. This paper explores the coping mechanisms of the senior high school learners during the disruptions at Goshen School of Technology and Humanities using a single case study. This research approach facilitates exploration of the phenomena within its context using Robert Yin's approach in the data analysis procedure to establish rigors of the research. Themes came out from the constructs of interviewees like senior high school learners who experienced anxiety, fear, mental health issues, technological, and social isolation; Covid-19 Pandemic affects the biological, psychological, and social aspects of the learners, and positive mindset, worthwhile activities, family and friends support, and daily routine are good coping strategies. The output of this study is the proposed new coping mechanism model to help the learners cope with their studies during the disruptions.